2019
DOI: 10.1111/jsr.12858
|View full text |Cite
|
Sign up to set email alerts
|

Link between insomnia and perinatal depressive symptoms: A meta‐analysis

Abstract: Evidence shows the possible link between insomnia and perinatal depressive symptoms. In order to find a convergent quantitative answer, we collected data via the search of Medline, EMBASE and reference tracking, which included nine studies (a total sample of 1,922 women). An aggregate effect size estimate (correlation coefficient) was generated using the comprehensive meta‐analysis software. For the meta‐analytic procedure, a random effects model was set a priori. Moderating factors, including study design, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 82 publications
(152 reference statements)
2
58
1
1
Order By: Relevance
“…Our observations highlight the key relation between intelligence, mental and physical health and sleep profile in healthy subjects. Previous work has implicated the important role of sleep on life functioning, such as cognitive performance and quality of life 7,8 , as well as higher rate of depressive symptoms 13,14 , hypertension, diabetes, and obesity 25,26 . Indeed, clear associations of sleep, cognitive performance and behavioral problems have been observed in children 53 , adults 54 , and elderly 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations highlight the key relation between intelligence, mental and physical health and sleep profile in healthy subjects. Previous work has implicated the important role of sleep on life functioning, such as cognitive performance and quality of life 7,8 , as well as higher rate of depressive symptoms 13,14 , hypertension, diabetes, and obesity 25,26 . Indeed, clear associations of sleep, cognitive performance and behavioral problems have been observed in children 53 , adults 54 , and elderly 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the quantity of sleep (sleep duration), quality of sleep includes sleep onset latency (i.e., time between going to bed and falling asleep), sleep efficiency (i.e., the percentage of time in bed during which someone is asleep), sleep disturbances, use of sleeping medication, and daytime dysfunction, all interacting with individual health and wellbeing 11,12 . Of note, it has been revealed that poor sleep quality is associated with higher rate of depressive symptoms in healthy subjects 13,14 ; and sleep disturbances are common in mood (e.g., major depression) and cognitive disorders 15,16 .…”
mentioning
confidence: 99%
“…Due to its chronic nature, insomnia usually leads to many negative outcomes, such as impaired daily functioning, lower quality of life, and poor mental health (3,14,15). For instance, insomnia commonly occurs with psychiatric disorders, especially depression, anxiety, and psychosis (16,17). In order to reduce its adverse outcomes and allocate appropriate health resources, health professionals and policymakers need to understand the patterns and clinical features of insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia occurs due to various causes, such as anxiety, emotional stress, and the inability to regulate emotions. On the other hand, insomnia could exacerbate stress, anxiety, and depression (9,10).…”
Section: Introductionmentioning
confidence: 99%